An overview of research groups and their activities in the field of inertial electrostatic confinement fusion - Wulfkühler, Jan-Philipp; Bakr, Mahmoud; Tajmar, Martin (Frontiers in Nuclear Engineering, 2025)
Inertial electrostatic confinement fusion has developed into a widespread academic field since its inception in the 1950s and 1960s. This paper provides an overview of the different research groups (universities and research institutes) and companies involved in the field of IECF and their scientific publications. A list of over 970 publications from 56 universities, 20 research institutes, and 25 companies was collected and analyzed. Also, an overview of the most common type of IECF devices, often referred to as “gridded” IECF device or “fusor” was created, including more than 30 devices. This paper serves as both a reference guide to the literature and the IECF devices.